If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 31 + -4x = 5x + 19 Reorder the terms: 31 + -4x = 19 + 5x Solving 31 + -4x = 19 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 31 + -4x + -5x = 19 + 5x + -5x Combine like terms: -4x + -5x = -9x 31 + -9x = 19 + 5x + -5x Combine like terms: 5x + -5x = 0 31 + -9x = 19 + 0 31 + -9x = 19 Add '-31' to each side of the equation. 31 + -31 + -9x = 19 + -31 Combine like terms: 31 + -31 = 0 0 + -9x = 19 + -31 -9x = 19 + -31 Combine like terms: 19 + -31 = -12 -9x = -12 Divide each side by '-9'. x = 1.333333333 Simplifying x = 1.333333333
| 22=8x+1-5X | | x^2+17x+31=4x-5 | | 24+-2a+3=7a | | 5(3-x)=-(1+x) | | x^2+x-18=2 | | -24=-4(k+3) | | 7h-7=17+4h | | y=x^2-7x+6 | | -2x+4=3(x-7) | | 21+9y-10=-277 | | 7x+9=8x+4 | | -7(x+9)=8x+42 | | 3(b+2)+2(x-5)=2 | | (2-z)(5z+3)=0 | | 5m+3=6m+7 | | 3(x+8)-8x=29 | | 3x^2=-6x-2 | | 9p+8q=100 | | 36x-4x+9+25x+7= | | (3x^2-6)=0 | | -(6(5xy+y^3)+5(9xy+7y^3))= | | -2a-11=7+7a | | 5x+5=-21-7x | | -3x^2-4x-5=0 | | 12p+6q=114 | | 2x*2x*2x+3x*3x*3x= | | 6a+2b=20 | | 160x-.8x^2=0 | | 200.00m+(-5600.00)=-2800.00 | | -5(x+5)=-15 | | 6p+4q=56 | | 3+2x=2(2+2x) |